2020
DOI: 10.1029/2019jb019076
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Investigation of the Foreshock Sequence of the 2010 Mw7.2 El Mayor‐Cucapah Earthquake

Abstract: Foreshocks can provide valuable information about possible nucleation process of a mainshock. However, their physical mechanisms are still under debate. In this study, we present a comprehensive analysis of the earthquake sequence preceding the 2010 M w 7.2 El Mayor-Cucapah mainshock, including waveform detection of missing smaller events, relative relocation, and source parameter analysis. Based on a template matching method, we find a tenfold increase in the number of earthquakes than reported in the Souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 65 publications
3
18
0
1
Order By: Relevance
“…Recent laboratory experiment and numerical modeling also indicated that creep can cause asperities to break seismically and cast stress disturbance on nearby faults, asperities and creep areas, which can in turn trigger new foreshocks (Cattania & Segall, 2021;McLaskey, 2019). A similar phenomenon of double-mechanism governing the earthquake initiation was also observed in the 2011 M W 5.0 Prague earthquake sequence (Savage et al, 2017), 2010 M W 7.2 EI Mayor-Cucapah earthquake sequence (Yao et al, 2020), and 2019 M W 5.8 Istanbul earthquake (Durand et al, 2020). In this study, we suggest the whole nucleation process of the 2021 Yangbi sequence is consistent with the rate-dependent cascade up model.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Recent laboratory experiment and numerical modeling also indicated that creep can cause asperities to break seismically and cast stress disturbance on nearby faults, asperities and creep areas, which can in turn trigger new foreshocks (Cattania & Segall, 2021;McLaskey, 2019). A similar phenomenon of double-mechanism governing the earthquake initiation was also observed in the 2011 M W 5.0 Prague earthquake sequence (Savage et al, 2017), 2010 M W 7.2 EI Mayor-Cucapah earthquake sequence (Yao et al, 2020), and 2019 M W 5.8 Istanbul earthquake (Durand et al, 2020). In this study, we suggest the whole nucleation process of the 2021 Yangbi sequence is consistent with the rate-dependent cascade up model.…”
Section: Discussionmentioning
confidence: 73%
“…The orange star indicates the mainshock. earthquake nucleation is more frequently observed in laboratory experiments and numerical simulations (e.g., Cattania & Segall, 2021;McLaskey, 2019;McLaskey & Lockner, 2014) than in field seismic data (e.g., Durand et al, 2020;Savage et al, 2017;Yao et al, 2020).…”
mentioning
confidence: 99%
“…However, additional preceding signals may have been missed by our autocorrelation procedure, which is less effective at detecting aseismic slips or slip events that are away from the earthquake hypocenter. It is possible that multiple processes have occurred concurrently and have modulated the nucleation process as a rate-dependent feedback system, which has been documented in experiments, simulations, and field observations (Cattania & Segall, 2021;McLaskey, 2019;Lapusta & Rice, 2003;Yao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…年 M w 7.6 Izmit 地震,Bouchon 等 [42] 发现震前存在重复地震。因此,他们认为地 震的成核是由蠕滑驱动的。而 Ellsworth 和 Bulut [43] 更为精细的观测表明,并没有 明显的证据表明存在重复地震,前震序列近乎是由西向东依次触发形成的,最终 产生主震,这与级联模型的描述相符。Yamashita 等 [44] 的实验结果显示,成核模 型依赖于断层的均匀程度:预滑模型适用于描述均匀断层的地震成核过程,而级 联模型则适用于非均匀断层。事实上,预滑和级联还可能同时在成核过程中起到 驱动作用 [30] 。近期,McLaskey [29] 通过实验揭示了这种现象,概念性地提出了第 三种成核模型--速度依赖的级联模型(rate-dependent cascade up model) 。该模 型认为,成核过程首先遵循预滑模型,并伴随有前震事件。但是,在预滑区扩展 到临界成核长度之前,某一个前震就可能直接触发整个断层的失稳。在天然地震 观测方面,也有关于这种复合成核模型的报道 [45] 。 第三,缺乏判别地震前兆的标准。例如,前兆性的慢滑移往往见于震例回溯 研究中;而现实的情况是,慢滑移是一种较为普遍的断层滑移行为,特别是在俯 冲带。那么,如何判别这些慢滑移是常规的慢滑移事件还是前兆性的预滑并预测 地震是一个国际性难题。 此外, 前震被普遍认为是地震的前兆, 但现实的情况是, 在分析地震活动性时,难以判断一个地震序列里是否已经包含了主震。Gulia 和…”
Section: )波速异常unclassified